Topical antibacterials in dermatology - Debabrata Bandyopadhyay (Wolters Kluwer Medknow Publications, 2021)
Topical antibacterials are commonly used for superficial pyodermas such as impetigo and treatment or prevention of infections following minor cuts, abrasions, burns, and surgical wounds. Several antibiotics and antiseptics are available for use in different indications. One of the major uses of topical antibacterials is acne in which benzoyl peroxide is the drug of the first choice either singly or in combination with antibiotics or retinoids. Mupirocin and fusidic acid are the two most commonly used antibiotics for the treatment of superficial pyodermas and eradication of staphylococcal carrier state. Bacterial resistance to topical antibiotics is a growing concern and topical antiseptics such as gentian violet are getting renewed interest as alternatives. Incidence of contact dermatitis is a limiting factor for the use of several topical antibacterials. Although many botanical products have demonstrated in vitro activities against skin pathogens, their clinical utilities remain to be established by good-quality clinical trials.